2018
DOI: 10.3390/nano8090723
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Potential Migration of Nanoparticles from Laponite-Polymer Nanocomposites

Abstract: In this study, the migration potential of laponite, a small synthetic nanoclay, from nanocomposites into foods was investigated. First, a laponite/ethylene vinyl acetate (EVA) masterbatch was compounded several times and then extruded into thin low-density polyethylene (LDPE) based films. This way, intercalation and partial exfoliation of the smallest type of clay was achieved. Migration of laponite was investigated using Asymmetric Flow Field-Flow Fractionation (AF4) with Multi-Angle Laser Light Scattering (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In our previous studies the diffusion (in polymer) controlled migration potential of TiN-NP [2], Ag-NP [1], and Laponite [3] from LD-PE-based composites was investigated. The same nanocomposites were now used to investigate the potential mechanical release of nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies the diffusion (in polymer) controlled migration potential of TiN-NP [2], Ag-NP [1], and Laponite [3] from LD-PE-based composites was investigated. The same nanocomposites were now used to investigate the potential mechanical release of nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study [3] it was demonstrated that AF4/MALLS was suitable for the characterization and quantification of laponite particles dispersed in an aqueous surfactant solution (2000 mg/L NovaChem). However, AF4/MALLS showed limitations caused by superimpositions in the fractogram when the sample matrix became too complex.…”
Section: • Laponite Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicological aspects of packaging nanomaterials are also covered in this Special Issue through the work of Bott and Franz [13], who studied nanoparticle migration from laponite–polymer nanocomposites. It is well-known that, in order to enhance the properties of nanoclay-containing polymeric nanocomposites, the nanoclays need to be properly exfoliated and intercalated within the polymeric matrix [2].…”
mentioning
confidence: 99%
“…Therefore, in this work, sample films with different laponite loadings were stored at high temperature (60 °C) to accelerate release, and migration in a food simulant was studied. No migration of laponite was detected once it was incorporated into the polymer matrix using a limit of detection of 22 µg laponite per Kg food, thereby assuring the safety of this specific material for food packaging applications [13].…”
mentioning
confidence: 99%